Da Hallyu ao ativismo Kpopper: apropriações táticas na plataforma twitter - Sacoman, Virgine Borges de Castilho (Universidade do Vale do Rio dos Sinos, 2022)
This thesis aims to analyze the uses and tactical appropriations through the Twitter platform by K-pop fans during the manifestations of the Black Lives Matter movement, that took place from May 2020. The investigation is guided by theoretical perspectives related to communication field, fan studies, fan activism, cyberactivism, tactical network uses and appropriations, platform studies and the configurations of Twitter. In order to understand the network tactics used by fans during the mobilizations, this thesis contextualizes Hallyu, since K-pop corresponds to a cultural product of the Korean wave, K-pop fan activism, fandom networking practices, the Black Lives Matter context, its history and the aspects of current structural racism in Brazil. The methodological construction for the empirical investigation is based on case study and netnography. The first was selected from the exploratory movement in which was delimited the platform to observe the mobilizations of K-pop fans. The netnography, by its turn, was important to investigate the actions of fanbases, fans and people who used tactics through Twitter. Then, online forms were developed aiming to understand the types and objectives that govern the tactics. Such methodological procedures contributed to the understanding of the tactical appropriations of Twitter carried by K-pop fans to engage the Black Lives Matter movement. The results point to tactics in which fans know the platform’s tools, are aware of the reach of their movements and understand the role of hashtags to engagement and its relevance to trend topics. It was also found that fans know how to use online petitions and fancams as collaborative practices and understand the importance of discourse and the care that must be taken with the platform’s tools for the success of network mobilizations.
Keywords: Estudos de fãs; Ativismo de fãs; Estudos da Hallyu; Ciberativismo; Apropriações táticas; Fan studies; Fan activism; Hallyu studies; Cyberactivism; Tactical appropriations; ACCNPQ::Ciências Sociais Aplicadas::Comunicação